Reproductive biology of a new invader, brown shrimp Crangon crangon (L), in Iceland - Puro, Helena, 1989- (2010)
Aspects of the reproductive biology of brown shrimp Crangon crangon were studied in Helguvík bay, southwest Iceland over a period of twelve months. C. crangon is a new invader in Iceland with first record in 2003. The life cycle and reproductive behaviour of C. crangon is not fully understood and even less is known about the Icelandic population. This paper tries to highlight the reproductive biology with comparison to other shrimp populations in Northern Atlantic. Size, fecundity, reproductive output, size-at-maturity and seasonal fluctuations were studied. A total 1060 shrimps from August 2009 to July 2010 were length and weight measured and sex was identified. Fecundity and reproductive output was determined for 30 shrimps and a comparison was done with the previous study of the same Helguvík population. Sex ratio was highly variable between months and within size classes but generally females were more numerous and dominating in biggest size classes. No correlation was found between female size and fecundity or reproductive output which differs from other studies done on brown shrimp.